2016
DOI: 10.1371/journal.pone.0151688
|View full text |Cite
|
Sign up to set email alerts
|

Selective Influences of Precision and Power Grips on Speech Categorization

Abstract: Recent studies have shown that articulatory gestures are systematically associated with specific manual grip actions. Here we show that executing such actions can influence performance on a speech-categorization task. Participants watched and/or listened to speech stimuli while executing either a power or a precision grip. Grip performance influenced the syllable categorization by increasing the proportion of responses of the syllable congruent with the executed grip (power grip—[ke] and precision grip—[te]). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Previously, we found that syllables (presented either auditorily, audiovisually or visually) are more likely categorized as [ke] when preparing a power grip and as [te] when preparing a precision grip [11]. We were, however, unable to determine whether perceptual processes were also affected.…”
Section: Discussionmentioning
confidence: 81%
See 4 more Smart Citations
“…Previously, we found that syllables (presented either auditorily, audiovisually or visually) are more likely categorized as [ke] when preparing a power grip and as [te] when preparing a precision grip [11]. We were, however, unable to determine whether perceptual processes were also affected.…”
Section: Discussionmentioning
confidence: 81%
“…We have also shown that the above-discussed articulation-grip connection works in a syllable categorization task [11]. In this study, participants were asked to prepare a power or a precision grip and then observe a noise-masked syllable.…”
Section: Introductionmentioning
confidence: 81%
See 3 more Smart Citations